Critical role of G3BP1 in bovine parainfluenza virus type 3 (BPIV3)-inhibition of stress granules formation and viral replication - Liu, Nian; Yang, Wei; Luo, Lingzhi; Ma, Mingshuang; Cui, Jin; Dong, Xiumei; Li, Yijing (Frontiers in Immunology, 2024)
Background It remains unclear whether BPIV3 infection leads to stress granules formation and whether G3BP1 plays a role in this process and in viral replication. This study aims to clarify the association between BPIV3 and stress granules, explore the effect of G3BP1 on BPIV3 replication, and provide significant insights into the mechanisms by which BPIV3 evades the host’s antiviral immunity to support its own survival. Methods Here, we use Immunofluorescence staining to observe the effect of BPIV3 infection on the assembly of stress granules. Meanwhile, the expression changes of eIF2α and G3BP1 were determined. Overexpression or siRNA silencing of intracellular G3BP1 levels was examined for its regulatory control of BPIV3 replication. Results We identify that the BPIV3 infection elicited phosphorylation of the eIF2α protein. However, it did not induce the assembly of stress granules; rather, it inhibited the formation of stress granules and downregulated the expression of G3BP1. G3BP1 overexpression facilitated the formation of stress granules within cells and hindered viral replication, while G3BP1 knockdown enhanced BPIV3 expression. Conclusion This study suggest that G3BP1 plays a crucial role in BPIV3 suppressing stress granule formation and viral replication.